Optimizing nitrogen fertilizer input using fallow season precipitation for dryland winter wheat - Shaobo Yu; Yimin Qu; Zhongdong Zhang; Zhiqiang Gao (Scientific Reports)
Abstract Precipitation is the major cause of yield variation in rainfed agriculture production on the Loess Plateau. Overfertilization is economically and environmentally undesirable. Optimizing nitrogen management based on fallow season precipitation is crucial for enhancing crop water use efficiency and achieving high yields in dryland/rainfed farming systems, considering the economic and environmental drawbacks of overfertilization and the uncertainty of crop yield and N input returns under high rainfall variability. Therefore, this study establishes a reference range that characterizes different wheat cultivation year types based on 37 years of fallow season precipitation data. The reference range for describing years as normal (220.7–346.2 mm), dry (< 220.7 mm), or wet (> 346.2 mm) is based on a 37-year precipitation record. At the same time, an 8 year field experiment (A randomized block design) was conducted using 7 N rates(0, 90, 120, 150, 180, 210, 240 kg N ha-1 to explore the prediction of PF on optimal N input for higher yield and water use efficiency (WUE). Optimum nitrogen (N) rates varied with the precipitation factor, being 150, 150–180, and 210 kg ha− 1 during dry, normal, and wet years respectively. Maximizing yield and water use efficiency (WUE) through optimized N input was primarily attributed to an increase in spike number per hectare. A non-linear regression analysis revealed a positive correlation between yield and precipitation frequency (PF), with an increase in yield ranging from 1.6 to 15 kg ha-1 for every mm increment in PF. Furthermore, the study demonstrated that an increase of 1% in the ratio of PF to total precipitation resulted in a significant yield gain of 46 kg ha-1.And as “drought at sowing” effects on yield were more adverse than “drought in growing season” effects in dryland systems, our results indicate that adjusting N fertilizer inputs based on summer rainfall variation could enhance wheat yield and WUE in the rainfed farming system. Thus, our results indicate that adjusting N fertilizer inputs based on seasonal variation in summer rainfall could enhance wheat yield and WUE in the rain-fed farming system.